Islam and Gender Issues in Indonesian Government Policy on the Protection of Female Migrant Workers in Malaysia - Muh. Nashirudin, M. Usman, Layyin Mahfiana, Mudofir (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
As the largest Muslim country in the world, Indonesia, being aware or unaware, represents the Islamic world. There are demands for social, political, and cultural life practices to be reflected in the form of good and fair social behaviors set forth in the forms of laws, regulations, and government policies. Islamic teachings, for example, greatly respect women and demand that their implementation becomes the responsibility of family, society, and state. Ironically, the problem of female migrant workers, especially in Malaysia, does not reflect the ideals that Islam aspires to. Female migrant workers are exposed to problems and their fate is very alarming for decades since the policy was implemented in the 1980s. Therefore, awareness for the improvement of their fate comes in the form of public criticism through mass media, scientific research in universities, and moral appeals of the intellectual elite of community organizations. This article highlights the government's policy on the protection of migrant workers in Malaysia and also discusses the role of Muslims in encouraging public and government awareness of the policy.